AN ANALYSIS OF FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S FOLKLORE ALBUM - Fitshafa Gustsa; Elisa Nurul Laili (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Abstract: In this research, the researcher used the descriptive qualitative method to analyze the data of figurative language and stylistics discovered in Taylor Swift's selected song lyrics on the Folklore album. This research is intended to find out the types and meanings of figurative language used in Folklore album, and to find out the types and functions of stylistics used in Folklore album. The researcher found some types of figurative language which is used in Folklore album there are Metaphor 12, Allegory 4, Metonymy 3, Verbal irony 7, Hyperbole 7, Personification 7, Symbol 14, Paradox 11, Simile 12, Synecdoche totem pro parte 1, and Understatement 1. Moreover, it is possible to conclude that figurative language and style of language significantly contribute to song lyrics. So that's why the writer or songwriter uses figurative language and any style of language in sentences to make the song more engaging and to assist readers to think more about the message and the meaning behind it.